2000
DOI: 10.1038/sj.onc.1203303
|View full text |Cite
|
Sign up to set email alerts
|

AP-2 transcription factors in the regulation of ERBB2 gene transcription by oestrogen

Abstract: Transcription of the ERBB2 oncogene is repressed by oestrogen in human breast cancer cells. We show that a 218 bp fragment of the human ERBB2 gene promoter is responsive to oestrogen in transient transfection in ZR75.1 and SKBR.3 cells when the oestrogen receptor is expressed. Deletion analysis of this fragment shows that a sequence located at the 5' end, which is known to mediate ERBB2 overexpression in breast cancer, is also responsible for the oestrogen response. This sequence binds AP-2 transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 33 publications
4
51
2
Order By: Relevance
“…Tamoxifen, which in an endogenous ER antagonist, may be affecting AP-2 regulation of ErbB2 transcription. 28 For the RE and RLE iTF ZF s, there is a retinoic acid-responsive element close to the CD54-31- ICAM-1) expression. CD54-31-scER-, -RE-and -RLE inducible zincfinger transcription factors (iTF ZF s) with either -VP64 and -KRAB (Krü ppel-associated box) domains were retrovirally expressed in HeLa cells for 2 days.…”
Section: Endogenous Regulation Of Multiple Genes With Tf Zf S L Magnementioning
confidence: 99%
“…Tamoxifen, which in an endogenous ER antagonist, may be affecting AP-2 regulation of ErbB2 transcription. 28 For the RE and RLE iTF ZF s, there is a retinoic acid-responsive element close to the CD54-31- ICAM-1) expression. CD54-31-scER-, -RE-and -RLE inducible zincfinger transcription factors (iTF ZF s) with either -VP64 and -KRAB (Krü ppel-associated box) domains were retrovirally expressed in HeLa cells for 2 days.…”
Section: Endogenous Regulation Of Multiple Genes With Tf Zf S L Magnementioning
confidence: 99%
“…Reduction in BST‐2 expression upon TGF‐β treatment correlates with enhanced AP2 binding to the BST‐2 promoter 123. AP2 is a transcription factor involved in repression of promoter sequences of at least one oncogene ERBB2 159. These findings suggest that in breast cancer cells, there is a progressive loss of TGF‐β signaling responsiveness that may result in aberrant BST‐2 overexpression.…”
Section: Bst‐2 Regulationmentioning
confidence: 97%
“…Studies have shown that E 2 -bound ESR1 represses ERBB2 transcription by competing for transcription factors such as NCOA1 (Bates & Hurst 1997, Perissi et al 2000. However, tamoxifen-bound ESR1 recruits NCOR allowing ERBB2 transcription to be activated (Newman et al 2000).…”
Section: S Pancholi Et Al: Erbb2 Influences Localization Of Esr1mentioning
confidence: 99%